Effect of Deamino-8-D-Arginine Desmopressin in Uremic Bleeding - Hong, Sae-Yong (Korean J Intern Med, 1996)
OBJECTIVES: This study is designed to evaluate the clinical outcome of uremic bleeding treated with DDAVP. DDAVP was given intravenously in nine ESRD patients who had undergone A/V fistula surgery and showed oozing of the operation site for more than one hour. METHODS: Hemostasis was observed by removing the blood from the wound site with a piece of filter paper for 3 hours after DDAVP administration. vWF, t-PA antigen, t-PA activity, total fibrinolytic activity in euglobulin fraction, fibrinopeptide A and FDP were measured before and after DDAVP administration. RESULTS: Cessation of the oozing did not occur within 3 hours after DDAVP administration in all of the cases. vWF levels and t-PA antigen were significantly increased after DDAVP administration peaked at 30 min for vWF and 60 min for t-PA antigen. t-PA activity increased in 6 cases and euglobulin fibrinolytic activity increased in 7 cases, respectively. These values fell towards pre-administration levels 120 min after the administration. There was no difference in fibrinopeptide A levels before and after DDAVP administration. FDP became positive in 4 cases after DDAVP administration. CONCLUSION: DDAVP increased both vWF and t-PA levels and cessation of the oozing from post-operative AV-fistula wounds did not occur within 3 hours after DDAVP administration in all of the cases. These results suggest that the effect of DDAVP should be reassessed in the treatment of uremic bleeding.